Pengaruh Kepribadian, Budaya Organisasi Dan Work Life Balance Terhadap Kepuasan Kerja Karyawan di PT. Sumatera Jaya Agro Lestari (PT.SJAL) SEI Lesung Estate - Alfian Alfian; Yunita Ria Ananda (Bata Ilyas Educational Management Review, 2026)
Purpose: The purpose of this study is to examine the influence of personality, organizational culture, and work-life balance on employee job satisfaction at PT. Sumatera Jaya Agro Lestari (Pt. Sjal) Sei Lesung Estate. This research is quantitative. Research Design and Methodology: Quantitative research is research that can be explained numerically and calculated using specific formulas, based on percentages and other statistical calculations. Data were collected through questionnaires distributed to 45 respondents using a total sampling technique, where all members of the population were sampled. The data sources in this study were primary and secondary data. Instrument testing (validity and reliability tests), classical assumption tests (normality tests, multicollinearity tests, and heteroscedasticity tests), multiple linear regression, and hypothesis testing (t-tests) were used using SPSS. Findings and Discussion: The results showed that personality had a positive and significant effect on employee job satisfaction, organizational culture had a positive and significant effect on employee job satisfaction, and work-life balance had a positive and significant effect on employee job satisfaction Implications: The findings suggest that PT Sumatera Jaya Agro Lestari should strengthen a positive organizational culture, support employees’ work-life balance, and improve personal development programs to enhance employee job satisfaction.